ANESTEZJOLOGIA I INTENSYWNA TERAPIAThe influence of anaesthetic and ischaemic preconditioning on generation of reactive oxygen species in the coronary sinus in coronary artery bypass graft patients - Goździk, Waldemar; Harbut, Piotr; Kübler, Andrzej; Jezierski, Adam; Goździk, Anna; Pelczar, Marek; Wysoczańska-Harbut, Joanna; Mierzchała, Magdalena; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Aim: This study on patients scheduled for elective coronary artery bypass graft surgery was designed to establish whether different preconditioning protocols affect the generation of coronary sinus sampled reactive oxygen species. Material and Methods: Thirty patients were randomized into three groups: anaesthetic preconditioning (APC) with 20 minutes of sevoflurane 2 vol% inhalation and 10 minutes washout before aortic cross-clamping (n = 10); ischaemic preconditioning (IPC) (n = 10), with 2 cycles of 2-minute ischaemia followed by 3-minute reperfusion before cross-clamping; or control without preconditioning (n = 10). ROS content was measured in coronary sinus blood: before cardiopulmonary bypass (CPB), 10 minutes after APC or IPC protocol or 10 minutes after CPB in the control group, and 10 minutes after aortic declamping in all groups. Electron paramagnetic resonance spectroscopy (EPR) was used to quantitatively measure ROS activation in coronary sinus blood. Lactate, interleukin-6, interleukin-10, and troponin I blood content was measured. Haemodynamic data were collected. Results: ROS generation in both preconditioning groups after protocol was significantly higher compared to control. It was 108% in the IPC and 96% in the APC group, compared to 64% in the control group. Interleukin-6 arterial blood concentration was significantly higher in all groups after surgery, but was significantly lower in the APC group, 83 (60.88-200.9) pg/ml, compared to the IPC, 177.46 (60.1-293.4) pg/ml, and control group, 200.81 (117.1-325.8) pg/ml, measured six hours after surgery. Conclusion: The results of the study may suggest that anaesthetic as well as ischaemic preconditioning increased ROS activity in coronary sinus blood, measured with EPR quantitative analysis, compared to control.